Attention Bias to Pain Words Comes Early and Cognitive Load Matters: Evidence from an ERP Study on Experimental Pain - Kangling Wang; Yifei Chen; Shimin Huang; Howe Liu; Wen Wu (Neural Plasticity)
Attention bias (AB) is a common cognitive challenge for patients with pain. In this study, we tested at what stage AB to pain occurs in participants with experimental pain (EP) and tested whether cognitive load interferes with it. We recruited 40 healthy adults aged 18-27 years, and randomized them into control and EP groups. We sprayed the participants in the EP group with 10% capsaicin paste to mimic acute pain and those in the control group with water, accessing both groups’ behavioral results and event-related potential data. We found that high-load tasks had longer response times and lower accuracies than low-load tasks did and that different neural processing of words occurred between the groups. The EP group exhibited AB to pain at an early stage with both attentional avoidance (N1 latency) and facilitated attention (P2 amplitude) to pain words. The control group coped with semantic differentiation (N1) at first, followed by pain word discrimination (P2). In addition, AB to pain occurred only in low-load tasks. As the cognitive load multiplied, we did not find AB in the EP group. Therefore, our study adds further evidence for AB to pain, suggesting the implementation of cognitive load in future AB therapy.